PEMBANGUNAN RUMAH DERET DALAM KEDUDUKAN HUKUM(STUDI KASUS DI RW 11 KELURAHAN TAMANSARI, KECAMATAN BANDUNG WETAN, KOTA BANDUNG) - Muhamad Fariq Kalam; Agus Rasyid Chandra Wijaya (INTELIGENSIA MEDIA, 2024)
This research is motivated by the disagreement between the Bandung City Government and the residents of RW 11 Tamansari Village, the Indonesian Government is trying to realize a program related to the recovery of slums. This research aims to explain how the efforts of RW 11 residents to reject the process of row house construction in the rule of law and to find out the legal certainty of RW 11 Tamansari residents in the construction of row houses. The method used in this research is a qualitative method with a descriptive approach. Data collection techniques in this research are observation, interview, and documentation. The results showed that residents refused because in terms of land ownership, the land in RW 11 Tamansari Village was not a regional asset and in legal certainty in the problems of residents of RW 11 Tamansari Village there were many violations of the rules that had been set, then the Bandung City Government ignored the rules themselves based on the incompatibility of Perwal No. 665 of 2017 to the process of building this row house.